Amino Acid Coordinated Self‐Assembly. Issue 4 (28th November 2017) - Zou, Qianli; Yan, Xuehai
Abstract: Self‐assembly of highly important biomolecules, such as proteins and peptides, has attracted tremendous interest in supramolecular construction of functional materials. However, as proteins and peptides are often immunogenic and their structures are complex, there is a strong demand to use amino acids as simpler building blocks. Still, mimicking the sophisticated structures and functions of natural materials by self‐assembly of simpler and more basic units of biomolecules, such as amino acids, remains a formidable challenge. Inspired by metal‐ion‐associated crystallization ofl ‐cystine in the urinary system, amino acid coordinated self‐assembly is discussed as an original strategy for supramolecular construction of biomimetic materials. The resulting materials possess the features of uniform size, hierarchical architecture, and structural resemblance to biological structures. In addition, the self‐assembly process can readily be adapted to simultaneous integration of various functional modules, providing materials with promising properties for biomimetic and biomedical applications. Abstract : A simple but versatile strategy for supramolecular construction of hierarchical materials is proposed. This novel strategy, namely amino acid coordinated self‐assembly, is based on the combination of coordination and other non‐covalent interactions by using amino acids and metal ions as the building blocks. The resulting materials show the advantages of uniform and controllable morphology, high stability, structural resemblance to biological structures, and tailored functionality.